Peningkatan Kesiapan Santri dalam Dunia Kerja Melalui Pelatihan Desain Curriculum Vitae Menggunakan Software AdobeIlustrator - Iis Hannani; Wida Rahayuningtyas (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of the PKM activity is to increase students' knowledge of the curriculum vitae as an important document that must be prepared when entering the world of work. It is hoped that with this curriculum vitae design training, students can have mature readiness when entering the world of work and reduce the unemployment rate. The method used is online training through zoom meetings with four stages of implementation (1) Explanation of curriculum vitae material, (2) Writing Biodata, (3) Searching for Design References, (4) Design and Improvement Process. The results obtained in this activity are an increase in knowledge about the curriculum vitae in students and the process of making it using the Adobe Illustrator application which can be seen from the results of the curriculum vitae designs that are designed.